Growth and properties of strained VOx thin films with controlled stoichiometry - Rata, Diana; Haverkort, Maurits W. (Arxiv, 2003)
We have succeeded in growing epitaxial films of rocksalt VOx on MgO(001) substrates. The oxygen content as a function of oxygen flux was determined using 18O2-RBS and the vanadium valence using XAS. The upper and lower stoichiometry limits found are similar to the ones known for bulk material (0.8<x<1.3). From the RHEED oscillation period a large number of vacancies for both vanadium and oxygen were deduced, i.e. ~16% for stoichiometric VO. These numbers are, surprisingly, very similar to those for bulk material and consequently quite strain-insensitive. XAS measurements reveal that the vacancies give rise to strong low symmetry ligand fields to be present. The electrical conductivity of the films is much lower than the conductivity of bulk samples which we attribute to a decrease in the direct overlap between t2g orbitals in the coherently strained layers. The temperature dependence of the conductivity is consistent with a variable range hopping mechanism.
Im Titel ist "x" tiefgestellt
Gesehen am 28.11.2017